Who Matters Most? The Effect of Parent's Schooling on Children's Schooling - Ira N. Gang (Rutgers University, Department of Economics, 1996)
This paper examines the differential effects of mother's schooling and father's schooling on the acquisition of schooling by their offspring. It does this in a 'cross-cultural' context by comparing results across three countries: Germany, Hungary and the Former Soviet Union. It looks within these countries, by gender, at different ethnic subgroups. Evidence is found, generally, that father's schooling is more important than mother's, but this does vary by ethnic group. Mother's schooling plays a relatively larger role for females.
Keywords: I21; J15; J62; 330; education; human capital; immigrants; parents; schooling